Towards a One Health Assessment of Artisanal and Informal Mining in Benue State, Nigeria - Samuel N. Paul; Chiara Frazzoli; Orish E. Orisakwe (Medical Sciences Forum)
This study evaluated the eco-health risk associated with exposure to lead (Pb) in mining sites in Benue State, Nigeria. Lead contamination was assessed in 48 water samples and 40 human blood samples. An Atomic Absorption Spectrophotometer was used for Pb analysis and ELISA kits for tumor necrosis factor-alpha (TNF-α) and kidney injury molecule-1 (KIM-1) analysis. A correlation was found between the blood Pb level (BLL) and the upregulation of KIM-1. The BLL of females was slightly higher than males, resulting in a higher inflammatory response through increased TNF-α levels. An increased inflammatory response due to chronic Pb exposure was observed with age. Miners and farmers around the mining sites recorded higher TNF-α levels compared to businesspeople, thus suggesting direct exposure to other mining-associated contaminants. Artisanal and informal mining impact environmental health and the Pb body burden.